The Role of Leadership in Driving Green HRM Initiative and Fostering an Environmentally Conscious Culture - R. V. Palanivel, Chanchal Sharma, Anjali Sharma, Yogesh Daudkhane (Journal of Informatics Education and Research, 2024)
Environmentally responsible human resource practices are the holy grail of the Green HRM movement, which aims to save the planet from impending ecological disasters. Sustainability in the environment is quickly gaining popularity. Using the direct interaction with workers, "green HR" aims to promote sustainable practices and increase employee awareness and commitments to the sustainability challenge. Organizations have benefited from eco-friendly HR initiatives such as electronic filing, car sharing, job sharing, teleconferencing, virtual interviews, recycling, telecommuting, online training, energy efficient office spaces, etc., which have helped employees engage more, save money, and work for the company longer. Implementing Green HRM may improve efficiency, which in turn may save operational expenditures, and it will also assist experts in the sector better fulfill their Corporate Social Responsibility. Employers and manufacturers may reap many rewards by embracing Green HRM. These include enhancing public impression of the organization and its goods, adopting ISO14000 standards, and conducting rigorous environmental audits. People in society and in the workforce will start to pay more attention to how natural resources are being used economically. The purpose of this study is to examine innovative environmentally conscious approaches to green HR practices and to draw attention to the importance of green HRM in polluting sectors.